A randomized clinical trial of cavity liners after selective caries removal: one-year follow-up - Stafuzza, Tássia Carina (J Appl Oral Sci, 2019)
Alternatives for the treatment of caries disease, such as minimally invasive approaches, have been developed in recent years. OBJECTIVE: To carry out clinical and radiographic evaluations of three cavity liners after selective caries removal. METHODOLOGY: Thirty-six primary molars with deep occlusal caries lesions without pulp involvement (from children of both genders, aged between 5 and 8 years) were randomly divided into the following groups: calcium hydroxide cement (CHC) group; mineral trioxide aggregate (MTA) group and Portland cement with added zirconium oxide (PCZ) group. The following-up period was 6- and 12-month. The clinical and radiographic success rates were evaluated through chi-square test. The radiographic measurements were compared by ANOVA followed by Tukey's test (p<0.05). RESULTS: Thirty-six patients were included, but thirty-four returned for 12-month follow-up. The overall success rate of the therapy for the three groups was 94.11% and no statistically significant differences occurred in the comparison among groups (p>0.05). Nineteen radiographs were selected to measure the dentin barrier thickness. The intragroup comparison presented a statistically significant increase of the dentin barrier for all groups, at 12-month follow-up. However, the MTA group showed increase of the dentin barrier, over time, 6- to 12-month follow-up. The intergroup comparison revealed no statistically significant differences (p>0.05). CONCLUSION: The clinical and radiographic data showed that all cavity liners provided effective treatment of primary teeth after selective caries removal.